The Influence of Leadership and Organizational Work Culture on Employee Performance Through Self-Efficacy - Deden Arifian Al Barq; Dudung Hadiwijaya; Priyo Susilo (Universitas Muhammadiyah Prof. DR HAMKA., 2025)
This study investigates how leadership and organizational work culture impact employee performance through self-efficacy, addressing the lack of research on psychological mediation in this relationship. Using a quantitative approach, data were collected from 145 Kopsyah Rabani employees via questionnaires and analyzed with SEM-PLS. Show that while leadership and work culture significantly enhance self-efficacy, they do not directly affect performance. Instead, self-efficacy fully mediates their influence, demonstrating its critical role in driving productivity. These findings emphasize that effective leadership and a supportive work environment boost performance by strengthening employees' self-belief. The study provides practical insights for organizations to prioritize employee confidence-building alongside leadership and cultural development for optimal performance outcomes